Managing and Utilizing the Funds of the Participants’ Fund Between the Doctrinal Proposals and the Models Proposed in Executive Decree No. 21-81 that Defines the Conditions and Modalities for Practicing Takaful Insurance - Younes, Badreddine (Finance and Business Economies Review, 2022)
The Takaful Participants Fund is one of the most important mechanisms invented by contemporary Islamic jurisprudence, in an attempt to distinguish Islamic Takaful insurance from conventional (commercial) insurance. The Algerian legislator referred to this type of insurance in the text of Article 203 bis of Ordinance No. 95-07 related to insurances, and then addressed its provisions in Executive Decree 21-81, which defines the conditions and modalities of practicing Takaful insurance. In this research, we will focus on studying the provisions related to the participants’ fund that came in the decree, especially those related to the way of managing and exploiting the funds, as well as how to distribute the insurance surplus for this fund.